Inspiratory Muscle Training Increases Insiratory Muscle Strength in Patients Weaning From Mechanical Ventilation: A Systematic Review - Moodie, L; Reeve, JC; Elkins, M (Australian Physiotherapy Association, 2011)
Question: Does inspiratory muscle training improve inspiratory muscle strength and endurance, facilitate weaning, improve survival, and reduce the rate of reintubation and tracheostomy in adults receiving mechanical ventilation? Design: Systematic review of randomised or quasi-randomised controlled trials. Participants: Adults over 16 years of age receiving mechanical ventilation. Intervention: Inspiratory muscle training versus sham or no inspiratory muscle training. Outcome measures: Data were extracted regarding inspiratory muscle strength and endurance, the duration of unassisted breathing periods, weaning success and duration, reintubation and tracheostomy, survival, adverse effects, and length of stay. Results: Three studies involving 150 participants were included in the review. The studies varied in time to commencement of the training, the device used, the training protocol, and the outcomes measured. Inspiratory muscle training significantly increased inspiratory muscle strength over sham or no training (weighted mean difference 8 cmH2O, 95% CI 6 to 9). There were no statistically significant differences between the groups in weaning success or duration, survival, reintubation, or tracheostomy. Conclusion: Inspiratory muscle training was found to significantly increase inspiratory muscle strength in adults undergoing mechanical ventilation. Despite data from a substantial pooled cohort, it is not yet clear whether the increase in inspiratory muscle strength leads to a shorter duration of mechanical ventilation, improved weaning success, or improved survival. Further large randomised studies are required to clarify the impact of inspiratory muscle training on patients receiving mechanical ventilation.